DAMPAK DEFORESTASI TERHADAP LUASAN RESAPAN AIR DI KECAMATAN BENGKONG, KOTA BATAM - Chaterina Jassira Syaputri; Dewi Liesnoor Setyowati; Fahrudin Hanafi (Universitas Pendidikan Ganesha, 2026)
Bengkong District, Batam City has experienced significant land cover changes from semi-forest areas to dense settlements. Rapid urbanization has led to high fragmentation of forest cover, reducing the area of natural infiltration and increasing surface runoff. This phenomenon raises concerns about the decrease in water storage potential that is crucial for community needs. This study aims to understand the impact of deforestation on the area of water infiltration in the region. The methods used include field surveys, questionnaires, documentation, and spatial analysis. Analysis was conducted through supervised classification and overlay techniques of land cover maps from 2013, 2018, and 2023 to identify changes in land use and the extent of deforestation. The results indicate that over a decade, 178.02 hectares or 82.84% of the forest has been converted, primarily into built-up land (148.71 ha) and open land (29.31 ha). The majority of conversion occurs in areas with high infiltration capacity. As a result, runoff increases by 54.90 mm (59.58%) and the potential water storage decreases by up to 55.19 mm (50.7%).